2007
DOI: 10.3358/shokueishi.48.83
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Improved Determination of Furan in Baby Foods and Infant Formulas by Headspace GC/MS

Abstract: Furan is a 5-membered ring compound with high volatility. The U.S. Food and Drug Administration (FDA) has recently published a report on the occurrence of furan in a large number of thermally processed foods. However, the FDA's analytical method, using standard curve addition, is not suitable for high-throughput routine laboratory operations. We developed a rapid and improved method for determination of furan in foods by headspace GC/MS. Quantification was achieved by using an internal standard of d 4 -furan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
4
5
0
Order By: Relevance
“…Preparations containing only fruits had the lowest furan content and the majority of samples in this group were below the detection limit. Our results correspond well to the ranges reported in previous surveys in Europe (Heppner and Schlatter 2007), Japan (Yoshida et al 2007), Switzerland (Zoller et al 2007) and the USA (Morehouse et al 2008).…”
Section: Food Additives and Contaminants 781supporting
confidence: 94%
See 1 more Smart Citation
“…Preparations containing only fruits had the lowest furan content and the majority of samples in this group were below the detection limit. Our results correspond well to the ranges reported in previous surveys in Europe (Heppner and Schlatter 2007), Japan (Yoshida et al 2007), Switzerland (Zoller et al 2007) and the USA (Morehouse et al 2008).…”
Section: Food Additives and Contaminants 781supporting
confidence: 94%
“…Taking into consideration a consumption of 234 g per day of canned baby food (Kersting et al 1998), Heppner andSchlatter (2007) assumed an exposure range of 50.03-3.5 mg kg À1 body weight (bw) day À1 , assuming a body weight of 7.5 kg for a 6-month-old baby. Yoshida et al (2007) reported levels of furan in a similar range of 1.4-90 mg kg À1 in 15 baby foods from the Japanese market. Most recently, the US FDA reported furan in ready-to-eat baby foods from the USA in the range 2.5-112 mg kg À1 (Morehouse et al 2008).…”
mentioning
confidence: 79%
“…In the present survey, the mean furan content in infant formulae was 3 µg/kg, which was lower than average results previously reported of 12 µg/kg (Crews and Castle, 2007) but within the range reported by Yoshida et al(2007). In the present survey, the mean furan content in infant formulae was 3 µg/kg, which was lower than average results previously reported of 12 µg/kg (Crews and Castle, 2007) but within the range reported by Yoshida et al(2007).…”
Section: Infant Foodsupporting
confidence: 49%
“…To be able to define better the efficiency of furan formation in food, a more realistic model system should be studied. Among numerous food products contaminated with furan, jarred baby foods are of particular concern due to the higher vulnerability of babies and infants to toxicants in general, combined with their high food intake to body weight ratio (Yoshida, Isagawa, Kibuna, Hamano-Nagaoka, & Maitani, 2007). Therefore, to mimic furan formation in baby foods, a simple model system based on starch was developed.…”
Section: Introductionmentioning
confidence: 99%